Prognostic role of EGFR gene copy number and KRAS mutation in patients with locally advanced rectal cancer treated with preoperative chemoradiotherapy - Bengala, C (Nature Publishing Group, 2010)
BACKGROUND: Epidermal growth factor receptor (EGFR), evaluated by immunohistochemistry, has been shown to have prognostic significance in patients with colorectal cancer. Gene copy number (GCN) of EGFR and KRAS status predict response and outcome in patients treated with anti-EGFR therapy, but their prognostic significance in colorectal cancer patients is still unclear. METHODS: We have retrospectively reviewed the baseline EGFR GCN, KRAS status and clinical outcome of 146 locally advanced rectal cancer (LARC) patients treated with preoperative chemoradiotherapy. Pathological response evaluated by Dworak's tumour regression grade (TRG), disease-free survival (DFS) and overall survival (OS) were analysed. RESULTS: Tumour regression grade 4 and TRG3–4 were achieved in 14.4 and 30.8% of the patients respectively. Twenty-nine (19.9%) and 33 patients (19.2%) had an EGFR/nuclei ratio >2.9 and CEP7 polisomy >50% respectively; 28 patients (19.2%) had a KRAS mutation. Neither EGFR GCN nor KRAS status was statistically correlated to TRG. 5-year DFS and OS were 63.3 and 71.5%, respectively, and no significant relation with EGFR GCN or KRAS status was found. CONCLUSION: Our data show that EGFR GCN and KRAS status are not prognostic factors in LARC treated with preoperative chemoradiation.